Selective Serotonin Reuptake Inhibitors and Clozapine: Clinically Relevant Interactions and Considerations - Amber N. Edinoff; Juliana M. Fort; Joshua J. Woo; Christopher D. Causey; Caroline R. Burroughs; Elyse M. Cornett; Adam M. Kaye; Alan D. Kaye (MDPI AG, 2021)
The monoamine hypothesis of depression attributes the symptoms of major depressive disorders to imbalances of serotonin, noradrenaline, and dopamine in the limbic areas of the brain. The preferential targeting of serotonin receptor (SERT) by selective serotonin reuptake inhibitors (SSRIs) has offered an opportunity to reduce the range of these side effects and improve patient adherence to pharmacotherapy. Clozapine remains an effective drug against treatment-resistant schizophrenia, defined as failing treatment with at least two different antipsychotic medications. Patients with schizophrenia who display a constellation of negative symptoms respond poorly to antipsychotic monotherapy. Negative symptoms include the diminution of motivation, interest, or expression. Conversely to the depressive symptomology of interest presently, supplementation of antipsychotics with SSRIs in schizophrenic patients with negative symptoms lead to synergistic improvements in the function of these patients. Fluvoxamine is one of the most potent inhibitors of CYP1A2 and can lead to an increase in clozapine levels. Similar increases in serum clozapine were detected in two patients taking sertraline. However, studies have been contradictory as well, showing no such increases, which are worrying. Clinicians should be aware that clozapine levels should be monitored with any coadministration with SSRIs.